MODEL PENGUATAN USAHA MELALUI KONSEP CREATIVE CAPITAL PADA USAHA KECIL MENENGAH (UKM) OLAHAN APEL DI KECAMATAN PUJON KABUPATEN MALANG - Asfiah, Nurul (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
This research is using survey methods and data collection techniques were used questionnaires and interviews. The tools analysis used is a SWOT analysis. IFAS analysis was used to determine the internal and external factors were analyzed using EFAS before. In processed apples SME obtained weights of 2 bigger than the disadvantages, with a weight of 1.28. The strength factors of the SME are corporate culture, key staff, access to natural resources, and operational efficiency. Weaknesses condition of SME, obtained with a weight of 1.28. The disadvantages were in form of organizational structure, corporate image, operational capacity, financial resources, exclusive contracts, market share, and product patents. The results described by EFAS analysis that the chances of SMEs processed apple with a weight of 1.62, while the weights for the threats faced by SMEs of 1.09, which indicates that the weight of greater opportunities than the threats received by SMEs processed apples.